PERAN KIYAI DALAM KEBIJAKAN LITERASI EKONOMI SYARIAH OLEH PEMERINTAH KABUPATEN SAMPANG - Muslihah, Muslihah; Anggreini, Diana Putri; Syafira, Anisa (STIS Darussalam Bermi, 2024)
This research aims to investigate the role of kiai in supporting the implementation of sharia economic literacy policies in Sampang Regency, as well as identifying the challenges faced in developing sharia economic literacy among the community. The approach used is qualitative research with a descriptive design, which collects secondary data through literature reviews, policy reports and previous research. Research findings show that kiai have an important role in strengthening sharia economic literacy in Sampang Regency. They are not only religious leaders, but also agents of change who educate the public regarding sharia economic principles. However, the role of kiai in this policy is still limited, especially in the planning and policy implementation stages. The collaboration between the Sampang Regency Government and Brawijaya University in the Doctoral Service program has had a positive impact in improving the abilities of kiai and broadening people's insight into sharia economics. This research concludes that to increase sharia economic literacy, it is important to provide special training for kiai and strengthen their involvement in planning and evaluating sharia economic policies.